PEMANFAATAN EKSTRAK KULIT PISANG KEPOK (Musa paradisiaca L) SEBAGAI BAHAN PENGAWET TELUR AYAM PETELUR - Frisca Wahyudi; Edya Moelia Moeis; Alfan Setya Winurdana (Universitas Islam Balitar, 2021)
Eggs easily experience a decrease in quality caused by physical damage, as well as evaporation of water, carbon dioxide, ammonia, nitrogen, and hydrogen sulfide from inside the egg. This study aims to find out the effect of giving banana peel extract (Musa paradisiaca L). effect on egg shrinkage, egg pH, and percentage of rotten eggs. The data was analyzed using RAL with treatment 4 and repeat 5. In the extract of banana peel by spraying several doses each experiment (4, 8.5, 12, 16) gr / 100 ml. The results of the study for the best value of each variable from 0-14 days are only treated at (P2) with a value (1,57 ± 0,29 ), this indicates that the extract dose of 8.5 gr / 100 ml is better. In this study it can be concluded that egg preservation with the utilization of banana peel extract with the addition of different extracts and storage for 14 days has not been able to inhibit the quality of eggs shown by the value of egg weight shrinkage, egg pH, and percentage of rotten eggs. It can be used as a reference base for future research, and further research is needed on the use of banana peel extract as a utilization of banana skin extract as a preservative of laying breed chickens